Climate warming alters thermal stability but not stratification phenology in a small north‐temperate lake. Issue 26 (19th December 2013) - Hadley, K. R.; Paterson, A. M.; Stainsby, E. A.; Michelutti, N.; Yao, H.; Rusak, J. A.; Ingram, R.; McConnell, C.; Smol, J. P.
Abstract Recent climate change represents one of the most serious anthropogenic threats to lake ecosystems in Canada. As meteorological and hydrological conditions are altered by climate change, so too are physical, chemical and biological properties of lakes. The ability to quantify the impact of climate change on the physical properties of lakes represents an integral step in estimating future chemical and biological change. To that end, we have used the dynamic reservoir simulation model, a one‐dimensional vertical heat transfer and mixing model, to hindcast and compare lake temperature‐depth profiles against 30 years of long‐term monitoring data in Harp Lake, Ontario. These temperature profiles were used to calculate annual (June–September) thermal stability values from 1979 to 2009. Comparisons between measured and modelled lake water temperature and thermal stability over three decades showed strong correlation (r2 > 0.9). However, despite significant increases in modelled thermal stability over the 30 year record, we found no significant change in the timing of the onset, breakdown or the duration of thermal stratification. Our data suggest that increased air temperature and decreased wind are the primary drivers of enhanced stability in Harp Lake since 1979. The high‐predictive ability of the Harp Lake dynamic reservoir simulation model suggests that its use as a tool in future lake management projects is appropriate. Copyright © 2013 John Wiley & Sons, Ltd.